Guatemala’s International Commission Against Impunity : A Case Study on Institutions and Rule of Law - Carrera, Fernando (World Bank, Washington, DC, 2017)
In the last years of the armed conflict, some of the actors that have participated in those clandestine operations re-adapted their modus operandi to fit other types of criminal activities such as customs corruption, large scale smuggling of goods, extortion and kidnapping for economic purposes, and drug trafficking. Control of borders and logistical corridors became also an important feature for their operations, which in turn led to political control of territories and linkages with politicians. In the last years of the armed conflict, some of the actors that have participated in those clandestine operations re-adapted their modus operandi to fit other types of criminal activities such as customs corruption, large scale smuggling of goods, extortion and kidnapping for economic purposes, and drug trafficking. Control of borders and logistical corridors became also an important feature for their operations, which in turn led to political control of territories and linkages with politicians. International Commission to Fight Impunity (CICIG) has played a critical role in using and promoting a legislative framework that enhances criminal prosecution in Guatemala. In this regard, some national laws have been critical for its work. First, the Law Against Organized Crime (LCCO) approved in 2006, before CICIG´s creation. However, CICIG requested the Guatemalan Congress to consider some reforms in 2009 to allow for more prosecutorial power, using instruments widely known in criminal law but inexistent in Guatemalan legal framework at that time. The reforms were approved, and since then CICIG and the Attorney General Office have used extensively their enhanced capacity.